PRINCIPLES AND FUNCTIONS OF MANAGEMENT OF PRODUCTION CAPACITY - Tursunov, Bobir (Journal of process management and new technologies, 2017)
The principles and functions of managing the production capacity are discussed in the article. On the part of the author, general and particular principles of managing the production capacity are classified, and another special principle of managing production capacity is proposed. The document more describes the management approach required for the Capacity Planning and Management, rather than going into the technical details. As such, it does not assume detail technical knowledge or go into the mathematical basis for performance modelling or testing.